Influence of Pulverized Lightweight Pumice Fine Aggregate on the Cement Mortar’s Dry Shrinkage (Journal of Engineering, 2025)
The use of lightweight aggregates in cement concrete manufacturing solves the issue of drying shrinkage over the concrete's life span; nevertheless, the use of artificial lightweight sand may increase this issue in the cement mortar. This research looks at how using lighter sand affects the non-mechanical qualities of cement mortar, namely the dry shrinkage property. It was prepared lightweight sand by pulverising pumice stone, screening it through a 1.18 mm sieve, and combining it with regular natural sand in varied amounts. It was tested various replacement percentages for lightweight sand by weight, such as 10%, 12%, 14%, 16%, and 18%, while keeping a single control sample without any lightweight pulverized pumice sand. As the proportion of pulverized pumice lightweight fine aggregate increases, the dry shrinkage of cement mortars containing pulverised lightweight pumice fine aggregate enhanced up to 161%, which has a negative impact on the durability of the cement mortar despite improved compressive and split tensile strengths of cement mortar. Moreover, the value of the brittleness index of the cement mortar reduced due to improvement of the split tensile strength. However, the bulk dry density of the cement mortar reduces up to 13.2%, which supports the reduction of the dead load in the high-rise buildings.